Coumarin derivatives ameliorate the intestinal inflammation and pathogenic gut microbiome changes in the model of infectious colitis through antibacterial activity - Jung, Hui-su; Park, Yei Ju; Gu, Bon-Hee; Han, Goeun; Ji, Woonhak; Hwang, Su mi; Kim, Myunghoo (Frontiers in Cellular and Infection Microbiology, 2024)
Coumarin, a phenolic compound, is a secondary metabolite produced by plants such as Tanga and Lime. Coumarin derivatives were prepared via Pechmann condensation. In this study, we performed in vitro and in vivo experiments to determine the antimicrobial and gut immune-regulatory functions of coumarin derivatives. For the in vitro antimicrobial activity assay, coumarin derivatives C1 and C2 were selected based on their pathogen-killing activity against various pathogenic microbes. We further demonstrated that the selected coumarin derivatives disrupted bacterial cell membranes. Next, we examined the regulatory function of the coumarin derivatives in gut inflammation using an infectious colitis model. In an in vivo infectious colitis model, administration of selected C1 coumarin derivatives reduced pathogen loads, the number of inflammatory immune cells (Th1 cells and Th17 cells), and inflammatory cytokine levels (IL-6 and IL-1b) in the intestinal tissue after pathogen infection. In addition, we found that the administration of C1 coumarin derivatives minimized abnormal gut microbiome shift-driven pathogen infection. Potential pathogenic gut microbes, such as Enterobacteriaceae and Staphylococcaceae, were increased by pathogen infection. However, this pathogenic microbial expansion was minimized and beneficial bacteria, such as Ligilactobacillus and Limosilactobacillus, increased with C1 coumarin derivative treatment. Functional gene enrichment assessment revealed that the relative abundance of genes associated with lipid and nucleotide metabolism was reduced by pathogen infection; however, this phenomenon was not observed in C1 coumarin derivative-treated animals. Collectively, our data suggest that C1 coumarin derivative is effective antibacterial agents that minimize pathogen-induced gut inflammation and abnormal gut microbiome modulation through their antibacterial activity.